The Babri Masjid question, 1528-2003 : a matter of national honour ; Vol: 2 - Noorani, Abdul Gafoor Abdul Majeed, 1930- (New Delhi : Tulika Books, 2003)
History of Babri Masjid of Ayodhya (Faizabad, India) through its demolition and resultant litigation in various fora; contributed articles and documents.
v.1. Ch. 1. The madness of revivalism -- Ch. 2. Myth, history and archaeology -- Ch.3. The nineteenth-century litigation -- Ch. 4. The Babri Masjid: 1886-1949 -- Ch. 5. How a Masjid was converted into a temple on 22-23 December 1949 -- Ch. 6. Prelude to the mosque's demolition, 1984-1992 -- v. 2. Ch. 7. Demolition of the Babri Masjid, 6 December 1992 -- Ch. 8. The CBI's chargesheet on the crime and the sessions judge's charges -- Ch. 9. Criminal proceedings, 1993-2003 --Ch. 10. The BJP's Ayodhya Campaign 1985-2003: misusing the name of Rama as symbol of Hindurva -- Ch. 11. The law's tortuous course: civil suits, 1950-2003 -- Ch. 12. Agreement of 12 October 1968 on the Shri Krishna Janmasthan.
Keywords: Babari Masjid (Faizabad, India) -- History; Hindu temples -- India -- Faizabad -- History; Ayodhya (Faizabad, India) -- Politics and government; Hindus -- India -- Faizabad; Muslims -- India -- Faizabad